Concomitant Autoimmune Diseases in Patients With Sarcoidosis in Turkey - Fidan YILDIZ; Şenol KOBAK; Hüseyin SEMİZ and Mehmet ORMAN (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the frequency and characteristics of autoimmune diseases associated with sarcoidosis patients. Patients and methods: The study included 131 sarcoidosis patients (36 males, 95 females; mean age 46.1 years; range, 20 to 82 years). Demographic, clinical, laboratory and radiological data of patients were evaluated retrospectively. The characteristics of autoimmune diseases associated with sarcoidosis (sarcoidosis-overlap group) patients and isolated sarcoidosis (isolated sarcoidosis group) were analyzed and compared. Results: Concomitant autoimmune diseases were detected in 15 (11.5%) (5 males, 10 females; mean age 50.8 years; range, 26 to 58 years) of the 131 patients with sarcoidosis and their mean disease duration was three months (range, 1 to 30 months). When compared with isolated sarcoidosis patients, more hand finger joint involvement, rheumatoid factor (RF) positivity, higher erythrocyte sedimentation rate (ESR) and less nonsteroidal anti-inflammatory drugs (NSAIDs) usage were found in the sarcoidosis-overlap group (p=0.035, p=0.049, p=0.015, p=0.018, respectively). There were no statistically significant differences between the two groups when evaluated for demographic, clinical parameters and disease-modifying antirheumatic drugs usage. Conclusion: Concomitant autoimmune diseases in patients with sarcoidosis may be rarely seen. These patients are characterized with more hand finger joint involvement, RF positivity, higher ESR and less NSAIDs usage. Multicenter, prospective studies involving large numbers of patients are needed to understand whether the association of sarcoidosis-autoimmune diseases is based only on coincidence or on a common etiopathogenesis.